# How to simplify this fraction?

## Homework Statement

I want the simplify the following equation

## Homework Equations

$\frac{x}{{p}^{2}}+\frac{n-x}{{(1-p)}^{2}}$, where p=$\frac{x}{n}$

## The Attempt at a Solution

I got this $\frac{{n}^{2}}{x}-\frac{{n}^{2}}{n-x}$, I don't think this is the right answer.

Last edited:

Related Precalculus Mathematics Homework Help News on Phys.org
HallsofIvy
Homework Helper
No, that is not the right answer. How did you get that?

No, that is not the right answer. How did you get that?
$=\frac{x{(1-p)}^{2}+{p}^{2}(n-x)}{{p}^{2}{(1-p)}^{2}}$
$=\frac{x}{{(\frac{x}{n})}^{2}}+\frac{n-x}{{(1-\frac{x}{n})}^{2}}$
$=x \frac{{n}^{2}}{{x}^{2}}+\frac{n-x}{({\frac{n-x}{n}})^{2}}$
$=\frac{{n}^{2}}{x}-(n-x)({\frac{n}{n-x}})^{2}$
$=\frac{{n}^{2}}{x}-\frac{{n}^{2}}{n-x}$

Did I make a mistake somewhere?

Last edited:
HallsofIvy
Homework Helper
$=\frac{x{(1-p)}^{2}+{p}^{2}(n-x)}{{p}^{2}{(1-p)}^{2}}$
$=\frac{x}{{(\frac{x}{n})}^{2}}+\frac{n-x}{{(1-\frac{x}{n})}^{2}}$
Why did you combine the fractions and then separate them again? In any case, the problem you posted had $1- p^2$, not $(1- p)^2$ which you now have.

$=x \frac{{n}^{2}}{{x}^{2}}+\frac{n-x}{({\frac{n-x}{n}})^{2}}$
$=\frac{{n}^{2}}{x}-(n-x)({\frac{n}{n-x}})^{2}$
$=\frac{{n}^{2}}{x}-\frac{{n}^{2}}{n-x}$

Why did you combine the fractions and then separate them again? In any case, the problem you posted had $1- p^2$, not $(1- p)^2$ which you now have.
I forgot to put parenthesis around 1-p in LaTex. It is fixed now.

@HallsofIvy (PF Mentor) Are you still here? What do you think?

SammyS
Staff Emeritus
Homework Helper
Gold Member
$=\frac{x{(1-p)}^{2}+{p}^{2}(n-x)}{{p}^{2}{(1-p)}^{2}}$
$=\frac{x}{{(\frac{x}{n})}^{2}}+\frac{n-x}{{(1-\frac{x}{n})}^{2}}$
$=x \frac{{n}^{2}}{{x}^{2}}+\frac{n-x}{({\frac{n-x}{n}})^{2}}$
You changed a "+" sign above to a "−" sign below.
$=\frac{{n}^{2}}{x}-(n-x)({\frac{n}{n-x}})^{2}$
$=\frac{{n}^{2}}{x}-\frac{{n}^{2}}{n-x}$

Did I make a mistake somewhere?